Is There a Need for Performance Measures for Cochlear Implant Centers?. (October 2015) - Vila, Peter M.; Hullar, Timothy E.; Buchman, Craig A.; Lieu, Judith E. C.
Performance measures (PMs), or quality indicators, are metrics based on objective data that allow one to assess whether a system achieves a prespecified goal. Given the relatively high level of resource utilization and potential morbidity associated with cochlear implantation (CI), PMs could be used to evaluate quality of care provided by implant centers and, ultimately, optimize care delivery. This article discusses PMs currently in use, how PMs are developed, potential downsides of using PMs, and various examples of PMs that could be used in CI centers.